2023
DOI: 10.1002/iid3.793
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Hepatitis B core antigen prevalence study in Kazakhstan

Abstract: Introduction Kazakhstan is being considered medium‐endemic for Hepatitis B virus infection (HBV). HBV remains transmissible by direct exposure to infected blood or organic fluids. This cross‐sectional study aimed to evaluate the prevalence of anti‐HBcore and the risk factors impacting positive anti‐HBcore markers among donors at Scientific‐Production Center of Transfusiology, Ministry of Healthcare of the Republic of Kazakhstan. Materials and Methods The samples taken from blood donors were tested for anti‐HBc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In Kazakhstan, the burden of viral hepatitis is substantial and continues to grow, as indicated by our findings and earlier scientific data 23 . Direct-acting antiviral hepatitis C drugs have not gained widespread use in Kazakhstan, and despite antiviral hepatitis B vaccination being included in the national vaccination schedule in 1998, the prevalence of anti‐HBcore antibodies was reported to be 17.2%, surpassing rates in many other countries 24 . Projections of viral hepatitis and liver cirrhosis until 2030 indicate a likely increase in the prevalence of these diseases, suggesting a rising demand for LTx.…”
Section: Discussionmentioning
confidence: 99%
“…In Kazakhstan, the burden of viral hepatitis is substantial and continues to grow, as indicated by our findings and earlier scientific data 23 . Direct-acting antiviral hepatitis C drugs have not gained widespread use in Kazakhstan, and despite antiviral hepatitis B vaccination being included in the national vaccination schedule in 1998, the prevalence of anti‐HBcore antibodies was reported to be 17.2%, surpassing rates in many other countries 24 . Projections of viral hepatitis and liver cirrhosis until 2030 indicate a likely increase in the prevalence of these diseases, suggesting a rising demand for LTx.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was conducted by the R software (version 4.1.1, USA, 2021) [14]. Descriptive statistics were reported as proportions (%) for categorical variables and as means±standard deviations for continuous variables.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies suggested that HBcAg could stimulate TLR signaling to produce proinflammatory cytokines, whereas HBeAg plays the opposite role [ 20 , 21 , 22 , 23 ]. Traditionally, anti-HBc is regarded as the indicator for past or ongoing HBV infections and is used as a blood screening test in HBV low-to-medium epidemic regions [ 24 , 25 ]. Notably, the anti-HBc level in most individuals with persistent, even resolved HBV infection usually exceeds the upper limit of routinely used qualitative anti-HBc assays.…”
Section: The Qanti-hbc Levels In the Natural History Of Hbv Infectionmentioning
confidence: 99%
“…In addition, several studies sug gested that HBcAg could stimulate TLR signaling to produce proinflammatory cytokines whereas HBeAg plays the opposite role [20][21][22][23]. Traditionally, anti-HBc is regarded as the indicator for past or ongoing HBV infections and is used as a blood screening test in HBV low-to-medium epidemic regions [24,25]. Notably, the anti-HBc level in most individual The upper part of the figure is divided into three regions that represent events and factors in the liver, peripheral blood, and immune system, while the lower half classifies the biomarkers at different dimensions.…”
Section: The Qanti-hbc Levels In the Natural History Of Hbv Infectionmentioning
confidence: 99%